Critical Representation: Mattering & Belonging for Students of the Global Majority - Rebecca E Haslam (Middle Grades Review, 2022)
Critical representation in literature and curricula requires an emancipatory agenda and examination of the ways in which people of diverse racial, cultural, linguistic, and other socially marginalized identities are portrayed, an assessment of how relevant, affirming, and accurate those representations are, and a consideration of the impact on a child’s sense of self and ‘other.’ This essay includes sample audit criteria for critical representation highlighting five sections: Storyline & Sense of Justice; Affirmation & Self-Worth; Relationships Among People; Author/Illustrator Background; and Language & Terminology, all with a focus on ‘mattering’ and holistic wellbeing of students of the global majority. Audit criteria explicitly engage questions of critical race theory such as: Does the storyline encourage passive acceptance of inequity, or active resistance against it? Are there messages that limit or damage a child’s aspirations or sense of self-worth? The essay concludes with examples of how practitioners are using the audit criteria to identify strengths, needs, and opportunities to improve their practice.
Keywords: critical representation; equity audit; mattering; literacy; literature